INVESTIGATION OF RESTORATION DIMENSIONAL PARAMETERS RODS PUMP GAS TRANSPORT PROCESS BY ELECTRIC- SPARK ALLOYING - Прунько, І.Б. (Problems of Tribology, 2014)
The working surfaces of the made from 40Kh steel push rods for oil-field pumps was treated by electric-spark buildup procedure using electrodes from T15K6 and VK8 alloys. The electric discharge between processed detail and elec-trode promotes to precipitation of the alloy elements and surface renewal. The high-strength surface layer with thickness 10…35 μm mainly containing the carbides was formed. Investigation of the surface layer structure at high resolution allow to study of surface morphology of treated detail.